2019
DOI: 10.3389/fgene.2019.01123
|View full text |Cite
|
Sign up to set email alerts
|

Association Study Between Methylation in the Promoter Regions of cGAS, MAVS, and TRAF3 Genes and the Risk of Cervical Precancerous Lesions and Cervical Cancer in a Southern Chinese Population

Abstract: A case-control study was used to explore the association between the methylation status in the promoter regions of the cGAS, MAVS, and TRAF3 genes and the diseases of cervical precancerous lesions (CPL) and cervical cancer (CC) in a Southern Chinese population, and to further explore their interaction effects with high-risk human papillomavirus (hrHPV) infection and environmental factors in these diseases. The study protocol was approved by the ethics committee of The First Affiliated Hospital of Jinan Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…DNA methylation of host genes and HPV-related genes in cervical epithelium played an important role in the diagnosis and treatment of cervical lesions [ 8 , 11 , 32 34 ]. In this study, we determined the value of DNA methylation marker panel ( ASTN1, DLX1, ITGA4, RXFP3, SOX17 and ZNF671 ) in detection of CIN lesions on cervical biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation of host genes and HPV-related genes in cervical epithelium played an important role in the diagnosis and treatment of cervical lesions [ 8 , 11 , 32 34 ]. In this study, we determined the value of DNA methylation marker panel ( ASTN1, DLX1, ITGA4, RXFP3, SOX17 and ZNF671 ) in detection of CIN lesions on cervical biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation level of more than 100 host genes is related to cervical cancer. Studies have found that CADM1, CDH1, DAPK1, EPB4L3, FAM19A4, MAL, PAX1, PRDM14 and TERT are among the most commonly methylated genes in cervical cancer and precancerous lesions [ 2 , 11 15 ]. At present, host cell DNA methylation analysis is mainly used for preliminary triage of hrHPV-positive women to detect cervical cancer and advanced CIN [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arginine methylation, a classified protein post-translational modification, is mediated by a member protein arginine methyltransferase, which furtherly regulates multiple signaling pathways [ 29 , 30 ]. Recently, it has been suggested that arginine methylation plays a critical role in regulating the replication of many viruses [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reference promoter sequence for the human WISP1 gene was obtained from the UCSC human genome browser and Ensembl genome browser, which is the widely recognized public platform for searching gene promoter sequence (Kent et al 2002;Aken et al 2017;Chadaeva et al 2019;Huang et al 2019). The methylated (M) and unmethylated (U) WISP1 promoter-specific primers were designed by MethPrimer following its published standards (Li and Dahiya 2002).…”
Section: Methylation-specific Polymerase Chain Reaction (Msp)mentioning
confidence: 99%